Internationalization of SME and entry mode choice in Brazil: the case study of Ameco, a French SME - Pelletier, Baptiste Jean Jeffrey (2013)
The research’s goal is to analyze, for a French SME, the attractiveness of two target markets in Brazil in order to support the CEO’s decision making on future investment. To face EU crisis, many French SMEs are currently seeking new opportunities around the world, especially in the BRIC countries. In fact, Brazil appears to be a promising market, offering numerous opportunities for growth. However, compared to traditional MNEs, SMEs have to deal with a lack of capabilities, market power and other resources. Going global is thus risky and costly for SMEs, which implies to evaluate carefully the viability of a foreign implementation. The analysis has revealed that Brazil is a market of approximately 30 million euros for the next 10 years. This is definitely a promising market for a company like AMECO. Taking into account these criteria, AMECO should open a representation office in the following year to canvass new clients and sign new contracts.